2010
DOI: 10.1007/s11738-010-0505-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of hydro-, chemo- , and hormonal-priming methods for imparting salt and PEG stress tolerance in Indian mustard (Brassica juncea L.)

Abstract: The present study was aimed to evaluate the effect of different seed priming methods to enhance the sodium chloride (NaCl) and polyethylene glycol-8000 (PEG-8000) stress tolerance in Indian mustard (Brassica juncea L.). Seeds subjected to different priming treatments such as water (hydro-priming), calcium chloride (CaCl 2 ) (chemo-priming), and abscisic acid (ABA) (hormonalpriming) showed increased rate of germination as compared to non-primed seeds. The primed and non-primed seeds were grown for 15 days and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 43 publications
(37 reference statements)
4
29
0
Order By: Relevance
“…Osmo-priming is a successful practice for improving seed germination performance under water stress, drought and salt stress. These results are reinforced by the previous study on improved germination by osmo-priming in wheat (Basra, Zia, Mehmood, Afzal, & Khaliq, 2002;Srivastava et al, 2010). In addition, the increase in priming indicator emergence with priming might be due to initiating metabolic events in primed seed which was corroborated by Elkheir et al (2016) mentioned that soaking rice seed in the water and PEG solutions 100 g L -1…”
Section: Effect Of Hydro and Osmo-priming Stress On Germination Percesupporting
confidence: 56%
See 1 more Smart Citation
“…Osmo-priming is a successful practice for improving seed germination performance under water stress, drought and salt stress. These results are reinforced by the previous study on improved germination by osmo-priming in wheat (Basra, Zia, Mehmood, Afzal, & Khaliq, 2002;Srivastava et al, 2010). In addition, the increase in priming indicator emergence with priming might be due to initiating metabolic events in primed seed which was corroborated by Elkheir et al (2016) mentioned that soaking rice seed in the water and PEG solutions 100 g L -1…”
Section: Effect Of Hydro and Osmo-priming Stress On Germination Percesupporting
confidence: 56%
“…Earlier reports have shown that seed priming was influenced by many complex interactions of factors and conditions such as plant species, water potentiality of priming agent, soaking duration in priming agent, variation of temperature, seed vigor and dehydration, and storage conditions of the primed seed (Hussain, Farooq, Basra, & Ahmad, 2006). Recent works reported a very comprehensive study on priming where seeds were treated by soaking in different priming agents and treatments such as abscisic acid (ABA) (hormonal priming), calcium chloride (CaCl2) (chemo-priming), and water (hydropriming), showing high performance rate of germination behaviors as compared to nonprimed seeds (Ghiyasi, Seyahjani, Tajbakhsh, Amirnia, & Salehzadeh, 2008;Srivastava et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, these compounds involved in osmotic adjustment differ widely among plant species in response to drought stress (Verslues and Bray 2006;Srivastava et al 2010). Consequently, our studies clearly revealed that the tolerant cultivar (IGPN 2004) showed the highest osmotic adjustment to severe water-deficit stress through more accumulation of proline, glycine betaine and total soluble sugars in comparison to moderately tolerant (IGP 76 and No.…”
Section: Discussionmentioning
confidence: 66%
“…Significant decrease in chlorophyll content of the cultivars exposed to 80 and 60% FC in comparison to 100% FC (Fig. 4a) might be attributed to the increased degradation of chlorophyll pigments due to stress-induced metabolic imbalance (Ashraf et al 1994;Srivastava et al 2010). Besides, the inhibitory effects of decreased water content on leaf development, reduced light interception and stomatal conductance leading to decrease in carbon assimilation (Medrano et al 2002;Fariduddin et al 2009) might have contributed to decreased chlorophyll content, which ultimately affect the transfer of photosynthetic assimilates from source to sink.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation